The prevalence of pre-hypertension and hypertension and their related metabolic or anthropometric parameters in rural elderly population in Northwest of Iran - Abbasalizad Farhangi, Mahdieh (Progress in Nutrition, 2017)
Methods: Data from the 248 elderly subject (n = 110 for men and 138 for women) were obtainedfrom the routinely collected health- center records in four health centers in rural areas in East Azarbayjan, Iran. Data on anthropometric and demographic variables were extracted from the health records. Joint National Committee ( JNC)-7 criteria were used to classify hypertension in participants. Results: There was a high prevalence of overweight and obesity (44.6% in men and 53.7% in women) and pre-hypertension (16.36% of men and 22.46% of women). Prevalence of hypertension in men and women was 30.90% and 34.04% respectively. Systolic blood pressure (SBP) was significantly correlated with body mass index (BMI) (r = 0.3; P = 0.019) and fasting serum glucose (FSG) (r = 0.3; P = 0.03) in men and women respectively. Conclusions: High prevalence of pre-hypertension and hypertension in the present study reinforced the need for routine evaluation of blood pressure for detecting the subjects at high risk of cardiovascular events and referring of vulnerable elderly subjects to other health care providers.